Combined use of key performance indicators and data envelopment analysis for the performance assessment of construction companies - Isabel Maria Noronha de Resende Horta (2009)
The traditional Construction Industry (CI) web benchmarking systems aredesigned to provide results based on key performance indicators, so a singlecompany performance measure is usually unavailable. This research aims tofulfil this gap by using Data Envelopment Analysis (DEA) as a method forcomplementing the information provided by the traditional assessments basedon performance indicators. The Portuguese CI web benchmarking system,icBench, was used to demonstrate the advantages of integrating bothapproaches. The analysis included a sample of 20 Portuguese leadingcontractors. The assessment of contractors described in this study adopted twodifferent perspectives: organizational performance and operations performance.Two types of DEA models were used for each perspective: one allows factorweights to vary freely and the other includes weight restrictions. The resultsobtained show that DEA can be a useful technique to identify efficientcompanies and to provide performance improvement targets for the others.